Canadian Strategies for Internationalization - Burnett, Sally-Ann; Huisman, Jeroen (International Higher Education, 2009)
The study of four comparable Canadian universities in Ontario, this article analyzed background documents from the government and the institutions, carried out site visits to the campuses of the institutions, and interviewed senior faculty and staff working in the area of internationalization. The main reasons for internationalizationparticularly international student recruitmentwere portrayed as the value of student diversity as well as revenue generation. The institutional cultures influence responses to globalization as well.